2011
DOI: 10.1117/12.898649
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cleaning on NIL templates: surface roughness, CD, and pattern integrity

Abstract: Nano-Imprint Lithography (NIL) is considered a promising alternative to optical lithography for technology nodes at 22nm hp and beyond. Compared to other advanced and complex lithography methods, NIL processing is simple and inexpensive making it a widely accepted technology for pattern media and a potential cost effective alternative for CMOS applications. During the NIL process, the template comes into direct contact with the resist on the substrate and consequently template cleanliness plays a decisive role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Pattern integrity of 250Gdpsi (50nm track pitch) BPM (Bit Patterned Media) templates under optimized MegaSonic conditions is also reported [5]. The template erosion under acid-free cleaning was previously reported on 65mm square (1/4" thick) templates and a CD loss of 0.05nm per clean was reported in year 2010 [6], which was further improved to 0.018nm per clean in year 2011 [4]. In this paper we present an even further improvement in non-acid process and demonstrate significant reduction in template erosion on DTR (Discrete Track Recording) and BPM patterns.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Pattern integrity of 250Gdpsi (50nm track pitch) BPM (Bit Patterned Media) templates under optimized MegaSonic conditions is also reported [5]. The template erosion under acid-free cleaning was previously reported on 65mm square (1/4" thick) templates and a CD loss of 0.05nm per clean was reported in year 2010 [6], which was further improved to 0.018nm per clean in year 2011 [4]. In this paper we present an even further improvement in non-acid process and demonstrate significant reduction in template erosion on DTR (Discrete Track Recording) and BPM patterns.…”
Section: Introductionmentioning
confidence: 69%
“…The SPM process is known to be very effective in removing organic residues however, concerns over silica erosion, residual ion control, waste chemical management and thermal cycling limits the use of SPM for NIL template cleaning. Previously HamaTech (SUSS MicroTec) has demonstrated a novel non-acid technique, taking advantage of efficient hydroxyl radical reaction with organics, for template resist removal [4]. Pattern integrity of 250Gdpsi (50nm track pitch) BPM (Bit Patterned Media) templates under optimized MegaSonic conditions is also reported [5].…”
Section: Introductionmentioning
confidence: 98%
“…Previously HamaTech (SUSS MicroTec) demonstrated a novel nonacid technique, taking advantage of efficient hydroxyl radical reaction with organics, for template resist removal. 4 Pattern integrity of 250 Gdpsi [50-nm track pitch (TP)] BPM (bit-patterned media) templates under optimized MegaSonic conditions were also reported. 5 The template erosion under acidfree cleaning was previously reported on 65-mm square (1∕4-in.…”
Section: Introductionmentioning
confidence: 92%
“…Consequently, mold cleaning using agents such as strong oxidants is necessary after a number of imprint cycles before a new layer of FSAM is applied [18][19][20]. However, recent studies have shown that the mold material itself (such as quartz) is vulnerable to strong oxidants with noticeable critical dimension (CD) loss during cleaning [21,22]. In the search for a damage-free mold cleaning process, several studies on an imprint resist with self-cleaning properties have been reported previously [11,23,24].…”
Section: Introductionmentioning
confidence: 99%